88 Association between area level material deprivation and incidence of hospitalization among children with SARS-CoV-2 in Montreal. (21st October 2022) - Abda, Assil; Drouin, Olivier; Kakkar, Fatima; Autmizguine, Julie; del Giorgio, Francesca; Gauvin, Lise
Abstract: Background: Although sociodemographic factors have been linked with SARS-CoV-2 infection and hospitalizations in adults, there are little data on the association between sociodemographic characteristics and SARS-CoV-2-related hospitalization in children. Objectives: The objective of this study was to determine the association between area-level material deprivation and incidence of hospitalization with SARS-CoV-2 among children. Design/Methods: We conducted a retrospective cohort study of all children (0-17 years of age) with a PCR-confirmed SARS-CoV-2 infection between March 1, 2020, and May 31, 2021, at a tertiary care pediatric hospital. Data were collected through chart review and included age, sex, and postal code. Postal codes were then assigned a dissemination area-level material deprivation score, measured via the Pampalon Material Deprivation Index (PMDI) quintiles. The Pampalon Material Deprivation Index (PMDI) uses postal codes to describe factors related to material deprivation obtained from the Canadian census, which are proxies for individual data in a geographic area. Specifically, the PMDI integrates data regarding (i) the proportion of persons without a high school diploma; (ii) the employment-to-population ratio; (iii) average personal income which is aggregated at the dissemination area level. We examined the association between PMDI quintiles and hospitalization using Poisson regression. Results: During the study period, 964 children had a positive PCR-confirmed SARS-CoV-2 test and 124 were hospitalized due to SARS-CoV-2 infection. Children from the most deprived PMDI quintile represented 31.6% of positive cases and 40.7% of hospitalizations (Figure 1 and 2). Both in bivariate and multivariable regression analyses, there was evidence of greater proportion of positive test results in the most deprived PMDI quintile (Quintile 5) compared to the least deprived quintile (Quintile 1) (rate ratio 1.77, 95%CI: 1.36; 2.62) (Table 1). The incidence of hospitalization due to SARS-CoV-2 infection was 2.42 times greater in the most deprived quintile compared to the least deprived quintile (95%CI: 1.33; 4.41) (table 1). In a post-hoc analysis, the risk for severe disease appeared higher for children living in Q5 areas relative to other areas but the difference did not reach statistical significance. Conclusion: In conclusion, in this study we found evidence that Canadian children living in neighbourhoods with high material deprivation had a higher incidence of infection and hospitalizations related to SARS-Cov-2 compared to children living in neighbourhoods with less material deprivation. Public health authorities should take these disparities into account when devising public health policy and interventions especially at this crucial point in the pandemic. Special efforts should be deployed to protect children from these more disadvantaged areas, especially as vaccination is not yet available to a majority of children.